Risk Differences Between Prediabetes And Diabetes According To Breast Cancer Molecular Subtypes. Issue 5 (30th September 2016) - Crispo, A.; Augustin, L.S.A.; Grimaldi, M.; Nocerino, F.; Giudice, A.; Cavalcanti, E.; Di Bonito, M.; Botti, G.; De Laurentiis, M.; Rinaldo, M.; Esposito, E.; Riccardi, G.; et al.
Abstract : Hyperglycemia and hyperinsulinemia may play a role in breast carcinogenesis and prediabetes and diabetes have been associated with increased breast cancer (BC) risk. However, whether BC molecular subtypes may modify these associations is less clear. We therefore investigated these associations in all cases and by BC molecular subtypes among women living in Southern Italy. Cases were 557 patients with non‐metastatic incident BC and controls were 592 outpatients enrolled during the same period as cases and in the same hospital for skin‐related non‐malignant conditions. Adjusted multivariate logistic regression models were built to assess the risks of developing BC in the presence of prediabetes or diabetes. The analyses were repeated by strata of BC molecular subtypes: Luminal A, Luminal B, HER2+, and Triple Negative (TN). Prediabetes and diabetes were significantly associated with higher BC incidence after controlling for known risk factors (OR = 1.94, 95% CI 1.32–2.87 and OR = 2.46, 95% CI 1.38–4.37, respectively). Similar results were seen in Luminal A and B while in the TN subtype only prediabetes was associated with BC (OR = 2.43, 95% CI 1.11–5.32). Among HER2+ patients, only diabetes was significantly associated with BC risk (OR = 3.04, 95% CI 1.24–7.47). Furthermore, when postmenopausal HER2+ was split into hormone receptor positive versus negative, the association with diabetes remained significant only in the former (OR = 5.13, 95% CI 1.53–17.22). These results suggest that prediabetes and diabetes are strongly associated with BC incidence and that these metabolic conditions may be more relevant in the presence of breast cancer molecular subtypes with positive hormone receptors. J. Cell. Physiol. 232: 1144–1150, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Hyperglycemia and hyperinsulinemia may play a role in breast carcinogenesis, and prediabetes and diabetes have been associated with increased breast cancer risk. However, whether BC molecular subtypes may modify these associations is less clear. Our results suggest that prediabetes and diabetes are strongly associated with BC incidence and these metabolic conditions may be more relevant in the presence of breast cancer molecular subtypes with positive hormone receptors.